Metal‐Organic Frameworks: Combining UV Lithography and an Imprinting Technique for Patterning Metal‐Organic Frameworks (Adv. Mater. 34/2013). (9th September 2013) - Doherty, Cara M.; Grenci, Gianluca; Riccò, Raffaele; Mardel, James I.; Reboul, Julien; Furukawa, Shuhei; Kitagawa, Susumu; Hill, Anita J.; Falcaro, Paolo
<x xml:space="preserve">Abstract</x> Patterning metal‐organic frameworks (MOFs) using cheap, fast, and versatile methods is a key enabling technology for multifunctional miniaturized device fabrication. A collaborative work led by Paolo Falcaro (CSIRO ‐ Australia) demonstrates on page 4701 how a combination of existing lithographic approaches, such as photolithography and imprinting, can be efficiently used for positioning different already‐prepared ultraporous crystals. Cover Image by Paolo Falcaro. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>